2021
DOI: 10.1111/crj.13358
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary team obviates biopsy in most patients with diffuse parenchymal lung diseases—A retrospective study from India

Abstract: Introduction:The inflammation and fibrosis in diffuse parenchymal lung diseases (DPLDs) in varied proportions give rise to different patterns in radiology and histopathology. The radiological pattern on CT of the thorax most often allows us to make a diagnosis with varying levels of confidence, to optimize management. With a multidisciplinary team bringing the strengths of their individual domains of knowledge, clinical, radiological, histopathological, and in many cases rheumatological, the level of confidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…25 A recent study also suggested that ILD-MDT meetings remove the need for a lung biopsy in many patients with DPLD. 26 The management of DPLD is strongly influenced by the early provisional diagnosis made by the ILD-MDT. This provisional diagnosis also frames the team's recommendations for the initial choice of pharmacological and nonpharmacological therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 A recent study also suggested that ILD-MDT meetings remove the need for a lung biopsy in many patients with DPLD. 26 The management of DPLD is strongly influenced by the early provisional diagnosis made by the ILD-MDT. This provisional diagnosis also frames the team's recommendations for the initial choice of pharmacological and nonpharmacological therapies.…”
Section: Discussionmentioning
confidence: 99%
“… 25 A recent study also suggested that ILD-MDT meetings remove the need for a lung biopsy in many patients with DPLD. 26 …”
Section: Discussionmentioning
confidence: 99%